Wayang Dawah and Religious Moderation in the Reconstruction of Contemporary Integrative Islamic Education - Agus Fatuh Widoyo; Ngatmin Abbas (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Religious moderation has become a strategic issue in contemporary Islamic education in Indonesia, particularly amid the rise of intolerance, extremism, and the weakening connection between religious learning and local culture. In this context, wayang dakwah serves as a cultural medium that bridges Islamic values, local wisdom, and socio-religious education. This study aims to analyze the role of wayang dakwah in internalizing religious moderation and to reconstruct an integrative paradigm of contemporary Islamic education based on cultural approaches. The study focuses on the construction of cultural da’wah, the internalization of moderation values, the role of dalang, and the educational implications of wayang dakwah in Boyolali Regency. This study employed a qualitative case study design. The research was conducted in Boyolali Regency from July to December 2025. Data were collected through in-depth interviews, observation, and documentation involving 10 dalang as informants, with Ki Sri Setyo as the key informant. Data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that wayang dakwah functions not merely as traditional performance art but also as a medium of cultural da’wah that effectively internalizes the values of tolerance, anti-violence, justice, deliberation, and respect for local traditions. Dalang play strategic roles as value educators, cultural mediators, public communicators, and agents of religious moderation. Wayang dakwah is relevant for strengthening religious moderation and reconstructing contemporary integrative Islamic education in a more contextual, humanistic, and transformative way.